2016
DOI: 10.5114/cipp.2016.63218
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Polish version of the Movement Imagery Questionnaire-3 (MIQ-3)

Abstract: backgroundImagery is often beneficial not only in gaining a psychological advantage when competing but also in building selfesteem and self-confidence. The aim of this study was to examine the reliability and validity of the Polish adaptation of the Movement Imagery Questionnaire-3 (MIQ-3), consisting of 12 questions measuring 3 dimensions: visual internal imagery, visual external imagery and kinesthetic imagery. participants and procedureA sample of athletes (N = 276 -102 women, 174 men (M = 21.25, SD = 6.35)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
4
5
0
Order By: Relevance
“…This specific type of imagery might be the consequence of previous experiences and training in both studied groups. This is in line with previous studies on athletes, including elite athletes, who reported higher imagery ability [15,16,48,49,50] compared to novices and nonathletes. Therefore, imagery is a skill that improves with practice [51], and elite athletes use it more frequently and deliberately [52].…”
Section: Discussionsupporting
confidence: 93%
“…This specific type of imagery might be the consequence of previous experiences and training in both studied groups. This is in line with previous studies on athletes, including elite athletes, who reported higher imagery ability [15,16,48,49,50] compared to novices and nonathletes. Therefore, imagery is a skill that improves with practice [51], and elite athletes use it more frequently and deliberately [52].…”
Section: Discussionsupporting
confidence: 93%
“…This analysis strongly differentiated among the three factors. The KI, IVI and EVI dimensions of the MIQ-3f confirmed the results obtained in previous studies (Budnik-Przybylska, Szczypińska, & Karasiewicz, 2016, Mendes et al, 2016. Second, the reliability of the MIQ-3f, which was evaluated in terms of internal consistency and repeatability, was very good.…”
Section: Discussionsupporting
confidence: 86%
“…Second, there are few practitioners in sports who are supposed to favor the use of IVI, such as those participating in slalom-based activities; thus, larger sample sizes should be considered in future research in which the test of concurrent validity should be included. Third, the test-retest interval used in the current study (i.e., more than two weeks) could be considered insufficient and thus favor the use of memory, although this interval is similar to that used in similar studies (Budnik-Przybylska et al, 2016;Loison et al, 2013;Lorant & Gaillot, 2004;Paravlić, Pišot, & Mitić, 2018 for examples). Finally, postquestionnaire interviews would have been necessary to control in greater detail whether/how participant made a clear distinction between IVI and KI.…”
Section: Discussionmentioning
confidence: 85%
“…Doubtful if FOLO could be used as external criterion. Sport Budnik-Przybylska et al 2016 [ 78 ] PL PO Athletes 276 21.3 102♀, 174♂ Construct validity- structural validity CFA with maximum likehood estimation confirmed the three-factor (external, internal and kinaesthetic) structure. χ 2 =76.98, df=51, CFI=0.93, GFI=0.89, AGFI=0.83, RMR=0.25, RMSEA=0.04 Very good + Accepted model fit: CFI, GFI >0.95, or SRMR <0.08, or RMSEA <0.06.…”
Section: Resultsmentioning
confidence: 95%
“… Sport Williams et al 2012 3 [ 31 ] CA E Athletes 97 19.5 58♀, 39♂ Internal consistency CR=0.89 external, 0.81 internal and 0.89 kinaesthetic AVE=0.66 external, 0.51 internal and 0.67 kinaesthetic Very good + Williams et al 2012 3 [ 31 ] = results of study 3. Sport Budnik-Przybylska et al 2016 [ 78 ] PL PO Athletes 47 NR NR Test-retest External r =0.70 Internal r =0.62 Kinaesthetic r =0.65 Doubtful Small sample size for this analysis. No information if the participants were stable.…”
Section: Resultsmentioning
confidence: 99%